Meu tio o Iauaretê: peculiaridades linguísticas e inovações linguageiras - Santos, Reginaldo Donizetti dos (2014)
Oral communication reigned absolute since the dawn of civilization until, with the cultures development, the emergence of writing revolutionized the way knowledge was recorded and preserved. In the quest to better understand the dichotomy between oral communication and writing, this paper discusses the linguistic peculiarities present in hinterland spontaneous language. Thus, it was decided to use as the corpus of the analysis in this thesis the tale Meu tio o Iauaretê, from the author João Guimarães Rosa (JGR), a natural of Minas Gerais, whose protagonist Tonho Tigreiro supposed metamorphoses into a jaguar that kills enemies merging revenge, hatred and regret, making use of an oral blending linguistic phenomena characterized by neologisms and onomatopoeia. From the review of the production of scholars on the subject as Preti, Bakhtin, Marcuschi, Ullmann among others, the objective of this study could be summarized in the following question: Which signs of orality present in the analyzed text feature the ordinary and everyday speech of the countryman and what are the most frequent linguistic peculiarities in there? Among the findings, it is observed that JGR celebrates cultural diversity and combat, by the language used in the text treatment, the possible biases in ordinary speech so common in the free use of orality and writing in everyday language practice, which also proposes a review of concepts like right , wrong , appropriate for the use of the language in certain communicative moments